An Adult Brain Atlas Reveals Broad Neuroanatomical Changes in Independently Evolved Populations of Mexican Cavefish - Loomis, Cody; Peuß, Robert; Jaggard, James B.; Wang, Yongfu; McKinney, Sean A.; Raftopoulos, Stephan C.; Raftopoulos, Austin; Whu, Daniel; Green, Matthew; McGaugh, Suzanne E.; Rohner, Nicolas; Keene, Alex C.; et al. (Frontiers in Neuroanatomy, 2019)
A shift in environmental conditions impacts the evolution of complex developmental and behavioral traits. The Mexican cavefish, Astyanax mexicanus, is a powerful model for examining the evolution of development, physiology, and behavior because multiple cavefish populations can be compared to an extant, ancestral-like surface population of the same species. Many behaviors have diverged in cave populations of A. mexicanus, and previous studies have shown that cavefish have a loss of sleep, reduced stress, an absence of social behaviors, and hyperphagia. Despite these findings, surprisingly little is known about the changes in neuroanatomy that underlie these behavioral phenotypes. Here, we use serial sectioning to generate brain atlases of surface fish and three independent cavefish populations. Volumetric reconstruction of serial-sectioned brains confirms convergent evolution on reduced optic tectum volume in all cavefish populations tested. In addition, we quantified volumes of specific neuroanatomical loci within several brain regions that have previously been implicated in behavioral regulation, including the hypothalamus, thalamus, and habenula. These analyses reveal an enlargement of the hypothalamus in all cavefish populations relative to surface fish, as well as subnuclei-specific differences within the thalamus and prethalamus. Taken together, these analyses support the notion that changes in environmental conditions are accompanied by neuroanatomical changes in brain structures associated with behavior. This atlas provides a resource for comparative neuroanatomy of additional brain regions and the opportunity to associate brain anatomy with evolved changes in behavior.